Rancang Bangun Penambahan Agitasi pada Alat Pengolah Limbah Fixer dengan Metode Elektrolisis - Efita Pratiwi Adi; R. Farzand Abdullatif; Zaroh Irayani; Hizas Azizi (Jurnal Teori dan Aplikasi Fisika, 2025)
The bubble layer that appears on the electrode causes the surface area of ​​the electrode that interacts with the electrolyte to decrease. This inhomogeneous bubble layer and electrolyte will inhibit the rate of electrolysis. One of the actions to reduce the bubble layer on the electrode and keep the electrolyte homogeneous is by agitation. This study aims to make modifications by adding agitation to the fixer solution waste processing tool with the electrolysis method. The container used is made of plastic with a diameter of 17 cm and a height of 19 cm. The electrodes used are made of 0.8 mm stainless steel with a width of 5 cm and a total length of 18 cm and the length that enters the fixer waste is about 13 cm with a distance between electrodes of 3.5 cm. The tool testing was carried out without agitation and with agitation. Each test will be carried out with voltage variations of 4V, 6V, 8V and 10V. Each test will use 3 liters of fixer waste with a time of 1 hour. The results of this study obtained that the designed tool can work well at a voltage of 4V to 10V and a capacity of 3L, with agitation proven to increase silver mass recovery up to 87.38% with a silver recovery rate at a voltage of 4V of 1.93 g/hour, at a voltage of 6V the silver recovery rate is 2.08 g/hour, at a voltage of 8V the silver recovery rate is 2.24 g/hour and at a voltage of 10V the silver recovery rate is 3.44 g/hour. Adding agitation to the fixer waste processing equipment, it can reduce the sulfidation that occurs and increase the silver mass significantly compared to without agitation. Keywords: Fixer waste, agitation, electrolysis, silver.